Influence of Organisational Culture and Management Support on Digital Transformation: Evidence from PT BNI KC Palopo, Indonesia - Mardhayanti Mardhayanti; Indra Kusdarianto; Suparni Sampetan (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study examines the influence of organizational culture (X1) and Management support (X2) on Digital Transformation (Y) at PT.BNI KC Palopo. Methodology: A quantitative explanatory survey was conducted involving 40 permanent employees using saturated sampling. Data were collected using five-point likert scale questionnaire and analyzed using multiple linear regression in SPSS. Results: Organizational culture showed no significant effect on digital transformation (β = 0.122, p = 0.367), while management support had a positive and significant effect (β = 0.692, p < 0.001). Together, the variables explained 49.5% of the variance (R² = 0.495). Findings: Management support is the branch level, whereas organizational culture has not yet contributed meaningfully. Novelty: This study highlights the strategic role of managerial commitment in supporting digital transformation within branch-level banking operations. Originality:  The findings offer practical insights for strengthening digital strategies through employee capacity building and the development of an adaptive work culture. Conclusion: Digital transformatio at PT.BNI KC Palopo is mainly driven by management support, while organizational culture remains less influential. Enhancing Iradership and employee readiness is essential to sustain digital progress. Type of Paper: Research Article